SOCS1 deficiency—crossroads of autoimmunity and autoinflammation—two case reports - Trojovsky, Kajetan; Seidl, Maximilian; Babor, Florian; Ehl, Stephan; Lee-Kirsch, Min Ae; Friedt, Michael; Laws, Hans-Juergen; Naami, Nibras; Oommen, Prasad Thomas; Ghosh, Sujal (Frontiers in Pediatrics, 2025)
Suppressors of cytokine signaling (SOCS) proteins play a critical role in regulating immune signaling pathways. Deficiency of SOCS1 leads to various autoimmune pathologies. We present two unrelated patients with distinct clinical manifestations. Patient 1, a 16-year-old male from Guinea, presented with Evans Syndrome, musculoskeletal pain and elevated liver enzymes. Patient 2, a 6-year-old German boy, developed recurrent oral aphthous ulcers, mild inflammatory bowel disease and chronic recurrent multifocal osteomyelitis. Both patients were diagnosed with SOCS1 deficiency by genetic testing. Treatment strategies included steroids, JAK inhibition and colchicine. These cases emphasize the importance of considering SOCS1 deficiency in patients with autoimmune or autoinflammatory diseases but also in patients with unexplained elevated IgE levels. They highlight the need for further research in ongoing multicenter registries to better understand this condition.